HUBUNGAN ANTARA SELF EFFICACY DAN DUKUNGAN SOSIAL TERHADAP FLOW AKADEMIK PADA SISWA - Dwi Viola, Firda; Yessy Elita; Arsyadani Mishbahuddin (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2025)
Abstract This study aimed to determine the relationship between self-efficacy and social support on academic flow in students. The population in this study were vocational high school students in Bengkulu City with a sample of 212 students taken using a simple random sampling technique. The instruments used were self-efficacy, social support, and academic flow questionnaires. Data analysis used multiple regression. The results of the study showed (1) there was a significant positive relationship between self-efficacy and academic flow in students with a correlation value of R = 0.125 (p <0.05), (2) there was a significant positive relationship between social support and academic flow in students with a correlation value of R = 0.684 (p <0.05), (3) there was a positive relationship between self-efficacy and social support on academic flow in students with a sig. 0.000 <0.05. The simultaneous relative contribution between self-efficacy and social support on academic flow was 59.9%. Therefore, it can be concluded that self-efficacy and social support have a positive relationship on academic flow Keywords: self efficacy, social support, academic flow